Putinismo rima com populismo? Uma análise do governo de Vladimir Putin a partir das contribuições de Ernesto Laclau - Pacheco, Caio César Albuquerque (2021)
This dissertation aims to understand if “putinism”, or yet, the regime headed by Vladimir Putin in Russia, could be called “populist” according to the idea carried out by Ernesto Laclau in “On populist reason” (2018). This scholar perceives populism in its ontological sense, which means, regardless of its ontic expressions. Therefore, the preliminary hypothesis assumed here is that putinism, just like “varguism”, “chavism” or “lulism”, can be considered an example of populism, one of the possible manifestations of this political logic. Such logic can be characterized by the division of social space into two large chains of equivalent and antagonistic demands. This division and articulation process between different social demands takes place along throughout the 2000s. Thus, the turning point that marks the beginning of Russian populism coincides with the popular manifestations of 2011-2012 and the election of Vladimir Putin for his third term in 2012.